2006
DOI: 10.1080/14767050600738396
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of n-3 fatty acids during pregnancy and lactation reduces maternal plasma lipid levels and provides DHA to the infants

Abstract: Maternal supplementation with n-3 fatty acids during pregnancy and lactation provides more DHA to the infant and reduces maternal plasma lipid levels compared to supplementation with n-6 fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 37 publications
4
53
0
6
Order By: Relevance
“…1). The present findings indicate that palatability of the FD for rats fed the LD during the dietary treatment period was higher than that of the FD at the beginning of the self-selection period, and this contributes to greater consumption of the FD compared to the LD because there are many reports that dietary fats are absorbed very effectively from the digestive tract and an increase in plasma n-3 FA content, particularly EPA and DHA, are observed after consumption of fish oil enriched diet (4,30,(33)(34)(35)(36). These results lead us to conclude that, at the beginning of the self-selection period, rats fed the LD consumed a larger amount of the FD than rats fed the FD diet to counteract the effect of an n-3 FA shortage during the experimental period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1). The present findings indicate that palatability of the FD for rats fed the LD during the dietary treatment period was higher than that of the FD at the beginning of the self-selection period, and this contributes to greater consumption of the FD compared to the LD because there are many reports that dietary fats are absorbed very effectively from the digestive tract and an increase in plasma n-3 FA content, particularly EPA and DHA, are observed after consumption of fish oil enriched diet (4,30,(33)(34)(35)(36). These results lead us to conclude that, at the beginning of the self-selection period, rats fed the LD consumed a larger amount of the FD than rats fed the FD diet to counteract the effect of an n-3 FA shortage during the experimental period.…”
Section: Discussionmentioning
confidence: 97%
“…We concluded that ALA in the PD failed to reduce the plasma lipid concentration. Although many reports also showed that diets enriched with fish oil reduce plasma TG concentration (30,(33)(34)(35), Finnegan et al reported that 4.5 and 9.5 g ALA intervention for 6 mo failed to reduce fasting and postprandial plasma lipid concentrations (33) and Barceleó-Coblijin et al reported that 3.6 g flaxseed oil intervention for 12 wk failed to reduce plasma lipid concentrations (4). It has been reported that dietary ALA can be converted to long-chain n-3 PUFA in animals and may reproduce some of the beneficial effects of EPAϩDHA (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…previous studies were only short term (13) or used fish oil during lactation [with (14) or without (15) supplementation during pregnancy as well]. To our knowledge, this is the first study to document the effects of high-dose fish oil supplementation during pregnancy on longitudinal changes in breast milk fatty acid composition over the first 6 mo of lactation.…”
mentioning
confidence: 79%
“…Since neonatal LCPUFA values can be influenced by maternal diet during pregnancy (van Houwelingen et al, 1995;Dunstan et al, 2004;Helland et al, 2006), maternal LCPUFA intake during pregnancy can be expected to influence later movement quality of the child. Indeed, maternal seafood consumption shows a positive relation with fine motor skills (Hibbeln et al, 2007).…”
Section: Discussionmentioning
confidence: 99%